2020
DOI: 10.1038/s41598-020-70727-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychological distress in the postnatal period in Japan: a population-based analysis of a national cross-sectional survey

Abstract: Mental health assessments of both members of a couple are important when considering the childrearing environment. the prevalence and factors associated with both parents' psychological distress have not been fully investigated. A nationally representative sample from the 2016 Comprehensive Survey of Living conditions in Japan was used to examine the prevalence of moderate and severe psychological distress in parents in the first year after childbirth. In total, 3,514 two-parent households raising children und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Postpartum depression, caused by unfamiliarity with child-rearing, is a mental illness suffered by some mothers [ 1 , 2 , 3 , 4 , 5 ]; approximately 10% of mothers experience depressive symptoms within one postpartum year [ 5 ]. Peak prevalence of postpartum depression, 13%, has been found to occur in the first three to four months postpartum [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum depression, caused by unfamiliarity with child-rearing, is a mental illness suffered by some mothers [ 1 , 2 , 3 , 4 , 5 ]; approximately 10% of mothers experience depressive symptoms within one postpartum year [ 5 ]. Peak prevalence of postpartum depression, 13%, has been found to occur in the first three to four months postpartum [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is imperative that mothers receive support to prevent depressive symptoms and facilitate bonding with their infant. In the context of Japan, a postpartum care project recently initiated by the government has begun to identify and treat women with postpartum depression within one month after giving birth; however, the incidence of postpartum depression has not yet decreased [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the disabled children in the present study were boys (70%) and had lowest severity (level 1) of disability (47%). This study found that the prevalence of psychological distress (17%) among fathers of disabled children aged 6–17 years is higher than among fathers (11%) of children below 1 year of age ( Takehara et al, 2020 ) as well as the overall prevalence of psychological distress (10.5%) in the Japanese population in 2016 ( Ministry of Health Labour and Welfare of Japan, 2017 ). We found a significantly higher odds ratio of psychological distress and poor subjective health status among fathers of disabled compared to non-disabled children.…”
Section: Discussionmentioning
confidence: 88%
“…The effectiveness of the Japanese version of K6 examined using areas under curve and stratum specific likelihood ratios (SSLR) demonstrated a likelihood ratio of greater than ten for a total K6 score of nine or more ( Furukawa et al, 2008 ). As a SSLR of 10 or more is considered highly effective in mental health screening, we used a cut-off of 9–24 to indicate psychological distress ( Furukawa et al, 2003 ; Ministry of Health Labour and Welfare of Japan, 2017 ; Schmitz et al, 2000 ; Takehara et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Before childbirth, it is thus necessary to gain knowledge about child-rearing and be aware of how a couple should raise a child. In Japan, research on postpartum depression has been conducted since the father"s pregnancy (Takehara, 2020). Parental depression during pregnancy can be a risk factor for attachment to the child.…”
Section: Research On Fathers In Pregnancymentioning
confidence: 99%